Periampullary Carcinoma-A Rare Histopathological Variant - Fazl QP,; Mozzain IK,; Shakeel ur RK,; Mubashir AS,; Sajjad AD,; Abdul Rashid L,; Zubaida R,; Zeba C, (Faculty of Medicine, UKM Medical Centre, 2015)
Signet ring cell adenocarcinomas may be encountered in various parts of gastrointestinal tract but are almost unheard of in the region of ampulla of vater. In the region of ampulla of vater even if we come across an adenocarcinoma, it is usually a well differentiated variant. A 56-year-old female with features of obstructive jaundice on evaluation was diagnosed to have a peri-ampullary carcinoma.The patient was subjected to a laparotomy. On exploration patient was found to have a malrotation of gut. Patient was subjected to a pylorus preserving pancreatico-duodenectomy. Histopathology of the resected specimen revealed a signet ring morphology which is a rare variant in periampullary region.